Panggilan untuk Mentauhidkan Allah dalam Al-Qurâan - Sani, Mukhyar (UIN Antasari Banjarmasin, 2014)
The onesess of God in the Quran gets very urgent and strategic position. Quran in calling people towards monotheism does not always use the command to the oneness of God, or prohibition to shirk, but sometimes use another approach, which invites people to understand the balance of the universe, as real evidence, that it is imposible to believe that God is not one, because it has the potential to make the regularity of this universe then by itself becomes a mess. Styles of call to monotheism are often accompanied by words that describe the attributes of God, such as the Compassionate, Most Loud, Maha Life and others